From macrophage to osteoclast - how metabolism determines function and activity - Hieke-Kubatzky, Katharina; Uhle, Florian; Eigenbrod, Tatjana (Cytokine, 2018)
Osteoclasts are specialised cells that resorb bone and develop from the monocyte/macrophage lineage. While there is a wealth of information on the regulation of macrophage function through metabolic activity, the connection between osteoclast differentiation and metabolism is less well understood. Recent data show that mitochondria participate in switching macrophages from an inflammatory phenotype towards differentiation into osteoclasts. Additionally, it was found that reactive oxygen species (ROS) actively take place in osteoclast differentiation by acting as secondary signalling molecules. Bone resorption is an energy demanding process and differentiating osteoclasts triggers the biogenesis of mitochondria. In addition, the activity of specific OXPHOS components of macrophages and osteoclasts is differentially regulated. This review summarises our knowledge on macrophage-mediated inflammation, its impact on a cell’s metabolic activity and its effect on osteoclast differentiation.